Filling the early Eocene gap of paguroids (Decapoda, Anomura): a new highly diversified fauna from the Spanish Pyrenees (Serraduy Formation, Graus-Tremp Basin). (January 2023) - Ferratges, Fernando A.; Artal, Pedro; van Bakel, Barry W.M.; Zamora, Samuel
Abstract: A highly diversified fauna of hermit crabs associated with reef environments from the Serraduy Formation (lower Eocene) in the southern Pyrenees (Huesca, Spain) is described. Other European Eocene outcrops have yielded paguroids associated with a single environment; however, the studied association represents one of the highest paguroid diversities in a single Eocene outcrop worldwide. The new material increases the diversity of known fossil paguroids, including eight species from which six are new: Clibanarius isabenaensis n. sp., Parapetrochirus serratus n. sp., Dardanus balaitus n. sp., ? Petrochirus sp., Eocalcinus veteris n. sp., ? Pagurus sp., Paguristes perlatus n. sp., and Anisopagurus primigenius n. sp. We erected a new combination for Paguristes sossanensis De Angeli and Caporiondo, 2009 and Paguristes cecconi De Angeli and Caporiondo, 2017 and transfer them to the genus Clibanarius . This association contains the oldest record of the genera Eocalcinus and Anisopagurus . Our data demonstrate that paguroids were diverse by the early Eocene in coral-reef environments and fill an important gap between the poorly known Paleocene assemblages and the more diverse mid- to late Eocene ones. UUID: http://zoobank.org/091f7a79-946c-4cd9-bdad-f727695e8503